1984
DOI: 10.1523/jneurosci.04-04-01086.1984
|View full text |Cite
|
Sign up to set email alerts
|

The effects of monensin on transport of membrane components in the frog retinal photoreceptor. I. Light microscopic autoradiography and biochemical analysis

Abstract: We have explored the use of the Na+-H+ ionophore monensin as a potential tool for the investigation of membrane assembly and transport in retinal photoreceptors. Autoradiographic analysis of frog retinas incubated with [3H]leucine in the presence of monensin revealed a lack of concentrated silver grains ("bands") at the base of the rod outer segments, in contrast to controls. This is indicative of a pronounced monensin-induced decrease in disc membrane assembly. Biochemical analyses of whole retinas and isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Total retinal proteins of individual halves were precipitated in ice-chilled 10% trichloroacetic acid (TCA), and the TCA-precipitable material was solubilized in 1 N NaOH. The specific radioactivity (disintegrations per minute per microgram protein) was determined by liquid scintillation counting and by fluorometric assay of protein content with fluorescamine (62), as described previously (35). The remaining half-retinas were pooled, solubilized in Laemmli sample buffer (31), and analyzed by polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate (SDS PAGE), by use of a discontinuous 7.5:15% gradient slab gel system as described in detail elsewhere ( 15,35).…”
Section: Microscopy and Autoradiographymentioning
confidence: 99%
See 2 more Smart Citations
“…Total retinal proteins of individual halves were precipitated in ice-chilled 10% trichloroacetic acid (TCA), and the TCA-precipitable material was solubilized in 1 N NaOH. The specific radioactivity (disintegrations per minute per microgram protein) was determined by liquid scintillation counting and by fluorometric assay of protein content with fluorescamine (62), as described previously (35). The remaining half-retinas were pooled, solubilized in Laemmli sample buffer (31), and analyzed by polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate (SDS PAGE), by use of a discontinuous 7.5:15% gradient slab gel system as described in detail elsewhere ( 15,35).…”
Section: Microscopy and Autoradiographymentioning
confidence: 99%
“…The specific radioactivity (disintegrations per minute per microgram protein) was determined by liquid scintillation counting and by fluorometric assay of protein content with fluorescamine (62), as described previously (35). The remaining half-retinas were pooled, solubilized in Laemmli sample buffer (31), and analyzed by polyacrylamide gel electrophoresis in the presence of sodium dodecyl sulfate (SDS PAGE), by use of a discontinuous 7.5:15% gradient slab gel system as described in detail elsewhere ( 15,35). Coomassie Blue staining and fluorography of gels was performed as previously described (15,35).…”
Section: Microscopy and Autoradiographymentioning
confidence: 99%
See 1 more Smart Citation
“…Opsin is initially glycosylated cotranslationally with mannose and N-acetylglucosamine in the endoplasmic reticulum, with subsequent posttranslational addition of N-acetylglucosamine in the Golgi apparatus (2,12,13). Recent studies (14,15) have shown that passage of opsin through the Golgi apparatus is obligatory for its incorporation into ROS disc membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Opsin is initially glycosylated cotranslationally with mannose and N-acetylglucosamine in the endoplasmic reticulum, with subsequent posttranslational addition of N-acetylglucosamine in the Golgi apparatus (2,12,13). Recent studies (14,15) have shown that passage of opsin through the Golgi apparatus is obligatory for its incorporation into ROS disc membranes.Biochemical studies have demonstrated both the formation of various intermediates and the presence of endogenous acceptors for those intermediates implicated in the lipid intermediate pathway of protein glycosylation in the retina (16). The biogenic activity of the lipid intermediate pathway is highest in the photoreceptor cells of the retina, relative to other retinal cell types (17).…”
mentioning
confidence: 99%